Competitive performance of Kenyan runners compared to their relative body weight and fat - Sengeis, M.; Müller, W.; Störchle, P.; Fürhapter-Rieger, A. (International Journal of Sports Medicine, 2021)
Body fat values obtained with various measurement methods deviate substantially in many cases. The standardised brightness-mode ultrasound method was used in 32 Kenyan elite long-distance runners to measure subcutaneous adipose tissue thicknesses at an accuracy and reliability level not reached by any other method. Subcutaneous adipose tissue forms the dominating part of body fat. Additionally, body mass (m), height (h), sitting height (s), leg length, and the mass index MI1 =0.53m/(hs) were determined. MI1 considers leg length, which the body mass index ignores. MI1 values of all participants were higher than their body mass indices. Both indices for relative body weight were within narrow ranges, although thickness sums of subcutaneous adipose tissue deviated strongly (women: 20-82 mm; men: 3-36 mm). Men had 2.1 times more embedded fasciae in the subcutaneous adipose tissue. In the subgroup with personal best times below world record time plus 10%, no correlation between performance and body mass index was found, and there was also no correlation with sums of subcutaneous adipose tissue thicknesses. Within the data ranges found here, extremely low relative body weight or low body fat were no criteria for the level of performance, therefore, pressure towards too low values may be disadvantageou